Positive electrode material and preparation method thereof, lithium ion battery and electric equipment

By preparing lithium manganese iron phosphate positive electrode material with specific pore structures and spherical structures, and adding carbon material during its preparation process, the problem of excessive slurry viscosity of the positive electrode material is solved, and better processing and electrochemical properties are achieved.

CN119650691APending Publication Date: 2025-03-18GUIZHOU CNGR XINGYANG ENERGY STORAGE TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411983967.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, the slurry viscosity of the lithium manganese iron phosphate positive electrode material is too high, resulting in serious processing difficulties in the processing of battery electrode sheets.

Method used

By preparing a specific positive electrode material, the total pore volume of the material is ≥0.25 cm3/g, the volume with a pore size of 0-100 nm accounts for no less than 70%, and carbon material is added during the preparation process to improve conductivity. The spherical and porous structure of this material facilitates the full infiltration of the electrolyte, while preventing the adhesive from entering the pores and reducing the viscosity of the electrode slurry.

Benefits of technology

The slurry viscosity of the positive electrode material is reduced, the uniformity and processing performance of electrode coating are improved, while maintaining high capacity, first-time charge and discharge efficiency and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650691A_ABST
    Figure CN119650691A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of positive electrode materials, in particular to a positive electrode material and a preparation method thereof, a lithium ion battery and electric equipment. The positive electrode material comprises lithium manganese iron phosphate; the total pore volume Vtotal of the positive electrode material is greater than or equal to 0.25 cm < 3 > / g; the ratio of the volume of pores with the pore diameter of 0-100nm of the positive electrode material to the total pore volume is Wd (0-100), and the Wd (0-100) of the positive electrode material is greater than or equal to 70%. When more 0-100 nm holes exist in the positive electrode material, sufficient infiltration of an electrolyte can be guaranteed, a binder can be prevented from entering the positive electrode material, and the positive electrode material is good in processability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to positive electrode materials and preparation methods thereof, lithium ion batteries, and electrical equipment. Background Art

[0002] As a positive electrode material for lithium-ion batteries, lithium manganese iron phosphate (LMFP) has the advantages of stable structure, high safety performance, good cycle performance and high discharge platform voltage. Its voltage platform is 4.1V, which is higher than the 3.4V of lithium iron phosphate, so it has a higher mass energy density (battery energy density = battery capacity * voltage platform / weight), which can break through the current upper limit of mass energy density of LFP positive electrode materials (increase by about 20%).

[0003] Mixing LMFP and NCM ternary materials as the positive electrode of lithium-ion batteries can fully utilize the high energy density of ternary materials and the excellent safety performance of LMFP materials. LMFP partially blocks the NCM / electrolyte interface, thereby alleviating the side reactions between NCM and the electrolyte, delaying the phase change of NCM during thermal runaway, reducing the heat generation between the charged cathode and the liquid electrolyte, and improving the safety characteristics of the battery.

[0004] In addition, because LMFP material exhibits a higher Li storage capacity in the charge and discharge window of NCM batteries, mixing LMFP into ternary materials will not significantly reduce the battery capacity while improving the battery safety performance. This mixing scheme takes into account the two key characteristics of the material's energy density and safety performance.

[0005] However, due to the presence of Mn element, the slurry viscosity of LMFP material is higher than that of lithium iron phosphate, ternary materials, etc., which makes it more difficult to process the battery pole pieces. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem of relatively serious processing difficulties in battery pole piece processing caused by excessively high slurry viscosity in the prior art for preparing positive electrode materials.

[0007] In order to achieve the above object, the first aspect of the present invention provides a positive electrode material, the positive electrode material comprises lithium manganese iron phosphate; the total pore volume of the positive electrode material is V 总 ≥0.25cm 3 / g; the proportion of the pore volume of the positive electrode material with a pore size between 0-100nm to the total pore volume is W d(0-100) , W of the positive electrode material d(0-100) ≥70%.

[0008] In some embodiments, the pore size distribution of the positive electrode material is 0 nm≤d≤200 nm.

[0009] In some embodiments, the total pore volume of the positive electrode material is 0.25≤V 总 ≤0.5cm 3 / g.

[0010] In some embodiments, the W of the positive electrode material d(0-100) ≥80%.

[0011] In some embodiments, the positive electrode material further includes a carbon material.

[0012] In some embodiments, based on the total weight of the positive electrode material, the content of the carbon material is 1.7 wt % to 2.5 wt %.

[0013] In some embodiments, the lithium manganese iron phosphate is of the general formula Li a Mn b Fe c PO4 represents, wherein, 1.00≤a≤1.12, b>0, 0.94≤b+c≤1.00; optionally, 0<b≤0.6.

[0014] In some embodiments, the cathode material satisfies at least one of the following conditions:

[0015] Condition a: The average pore size of the positive electrode material is 40nm≤d 平均 ≤55nm, optionally, 45nm≤d 平均 ≤55nm;

[0016] Condition b: The median pore size of the positive electrode material is 40nm≤d 中位 ≤60nm;

[0017] Condition c: The compaction density of the positive electrode material is ≥ 2.0 g / cm 3 ;

[0018] Condition d: The specific surface area of ​​the positive electrode material is 10-27m 2 / g, optionally, 20-25m 2 / g.

[0019] A second aspect of the present invention provides a method for preparing a positive electrode material, the method comprising:

[0020] The slurry 1 containing the lithium source, the manganese source, the iron source, the phosphorus source and the first part of the carbon source is subjected to sand milling treatment I, drying treatment I and sintering treatment I to obtain a precursor;

[0021] The slurry 2 containing the precursor and the remaining carbon source is subjected to sand milling treatment II, drying treatment II and sintering treatment II to obtain the positive electrode material;

[0022] The first part of carbon source accounts for 40wt%-80wt% of the total carbon source.

[0023] In some embodiments, the total carbon source includes glucose and PEG.

[0024] It should be noted that the compositions of the first part of the carbon source and the remaining part of the carbon source in the present invention are consistent. The present invention is only expressed as the first part of the carbon source and the remaining part of the carbon source in order to express that the entire carbon source is added to the reaction system in at least two parts. Those skilled in the art should not understand this as a limitation on the scheme of the present invention.

[0025] In some embodiments, based on the total weight K of the lithium source, manganese source, iron source and phosphorus source in the slurry 1, the mass of the glucose is 5wt%K-12wt%K, and the mass of the PEG is 1wt%K-5wt%K.

[0026] In some embodiments, the method satisfies at least one of the following conditions:

[0027] Condition A: The solid content of the slurry 1 is 18wt%-48wt%;

[0028] Condition B: The sanding treatment I is performed for 8-12 hours;

[0029] Condition C: the solid content of the slurry 2 is 18wt%-48wt%;

[0030] Condition D: The sanding treatment II is performed for 6 h to 10 h;

[0031] Condition E: the drying treatment I and the drying treatment II are spray drying treatments; optionally, the conditions of the spray drying treatment are selected from: an inlet air temperature of 180-280° C., and an outlet air temperature of 60-160° C.;

[0032] Condition F: The conditions of the sintering treatment I and the sintering treatment II are selected from: temperature of 300-800° C. and time of 5-12 h.

[0033] In some embodiments, the present invention also provides a positive electrode material prepared by the method described in the second aspect.

[0034] The third aspect of the present invention provides a lithium ion battery, comprising the positive electrode material described in the first aspect and / or the positive electrode material prepared by the method described in the second aspect.

[0035] A fourth aspect of the present invention provides an electrical device, comprising the lithium-ion battery as described in the third aspect.

[0036] The positive electrode material of the present invention has a special spherical shape and pore structure morphology, and its total pore volume V 总 ≥0.25cm 3 / g, and the volume of pores with a pore size of 0-100nm accounts for no less than 70%, indicating that this material contains a large number of pores with small pore sizes. This structure is conducive to the full infiltration of the electrolyte, while hindering the binder from entering the pores, reducing the viscosity of the electrode slurry and improving the uniformity of electrode coating. In addition, the presence of fewer large pores makes the surface of the spherical particles relatively smooth, which can further improve the slurry effect of the material during the preparation of the positive electrode sheet.

[0037] The positive electrode materials obtained in the present invention all show relatively high capacity, initial charge and discharge efficiency and rate performance, and in particular, have significantly improved processing performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Example 1 ( Figure 1 a, magnification is 3k; Figure 1 b, magnification is 50k) and comparative example 1 ( Figure 1 c, magnification is 3k; Figure 1 d, scanning electron microscope (SEM) result of the prepared lithium manganese iron phosphate positive electrode material (magnification is 50k).

[0039] Figure 2 Example 1 ( Figure 2 a, magnification is 3k; Figure 2 b, magnification is 50k) and comparative example 1 ( Figure 2 c, magnification is 3k; Figure 2 d, cross-sectional polishing-scanning electron microscopy (CP-SEM) result of the prepared lithium manganese iron phosphate positive electrode material (magnification 50k).

[0040] Figure 3 Example 1 ( Figure 3 a), Example 2 ( Figure 3 b), Comparative Example 1 ( Figure 3 c) and Comparative Example 2 ( Figure 3 d) Result diagram of nitrogen adsorption and desorption pore volume of the prepared lithium manganese iron phosphate positive electrode material.

[0041] Figure 4 This is the XRD of the lithium manganese iron phosphate positive electrode material prepared in Example 1 and Comparative Example 1.

[0042] Figure 5 This is the rate performance curve of the lithium manganese iron phosphate positive electrode material prepared in Example 1.

[0043] Figure 6 This is the rate performance curve of the lithium manganese iron phosphate positive electrode material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0044] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0045] As mentioned above, the first aspect of the present invention provides a positive electrode material, the positive electrode material comprises lithium manganese iron phosphate; the total pore volume of the positive electrode material is V 总 ≥0.25cm 3 / g; the proportion of the pore volume of the positive electrode material with a pore size between 0-100nm to the total pore volume is W d(0-100) , W of the positive electrode material d(0-100) ≥70%.

[0046] In some embodiments, the total pore volume of the positive electrode material is, for example, 0.25 cm 3 / g, 0.30cm 3 / g, 0.35cm 3 / g, 0.40cm 3 / g, 0.45cm 3 / g, 0.50cm 3 / g, 0.60cm 3 / g, 0.70cm 3 / g or ≥0.25cm 3 / g; W of the positive electrode material d(0-100) For example: W d(0-100) ≥71%, W d(0-100) ≥72%, W d(0-100) ≥73%, W d(0-100) ≥74%, W d(0-100) ≥75%, W d(0-100) ≥76%, W d(0-100) ≥77%, W d(0-100) ≥78%, W d(0-100) ≥79%, W d(0-100) ≥80%.

[0047] The W d(0-100)) =V d(0-100) / V 总 ; Among them, V d(0-100) Indicates the pore volume with pore diameter between 0-100nm; V 总 represents the total pore volume.

[0048] A large total pore volume is beneficial to improving the wettability of the electrolyte, but the presence of large pores allows the binder to enter, which is not conducive to reducing the viscosity of the electrode slurry; in the slurrying process of the electrode sheet preparation, pores larger than 100nm are prone to adsorb the binder, resulting in too high slurry viscosity, while pores smaller than 100nm can prevent the binder from entering. The total pore volume V of the positive electrode material of the present invention 总 ≥0.25cm 3 / g, and the volume of pores with a pore size of 0-100nm accounts for no less than 70%, indicating that this material has a large number of pores with small pore sizes. This structure is conducive to the full infiltration of the electrolyte, while hindering the binder from entering the pores, reducing the viscosity of the electrode slurry, improving the uniformity of the electrode coating, and is conducive to improving the capacity and rate performance.

[0049] In the present invention, due to the lack of macropores, the surface of the spherical particles is relatively smooth. On the basis of preparing the material into spherical particles, the density of the primary particle stacking is increased to make the surface of the spherical particles smooth, which can further improve the slurry effect of the material in the process of preparing the positive electrode sheet.

[0050] In some embodiments, the pore size distribution of the positive electrode material is 0 nm≤d≤200 nm.

[0051] In some embodiments, the total pore volume of the positive electrode material is 0.25≤V 总 ≤0.5cm 3 / g.

[0052] If the total pore volume of the positive electrode material is too large, it is easy to form more macropores; if the total pore volume is too small, it is not conducive to the full infiltration of the positive electrode material in the electrolyte.

[0053] In some embodiments, the W of the positive electrode material d(0-100) ≥80%, e.g. W d(0-100) It is 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89% and 90%.

[0054] In some embodiments, the positive electrode material further includes a carbon material.

[0055] In some embodiments, based on the total weight of the positive electrode material, the content of the carbon material is 1.7wt% to 2.5wt%; for example, the content of the carbon material is 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, or 2.5wt%.

[0056] In the present invention, the content of the carbon material within this range is beneficial to improving the conductivity of the positive electrode material, too low a carbon content is not conducive to the conductivity of the positive electrode material, and too high a carbon content is not conducive to the capacity of the positive electrode material.

[0057] The carbon content in the present invention is tested using an infrared carbon-sulfur instrument, and the specific test method refers to the national standard (GBT20123-2006).

[0058] In some embodiments, the lithium manganese iron phosphate is of the general formula Li a Mn b Fe c PO4 represents, wherein, 1.00≤a≤1.12, b>0, 0.94≤b+c≤1.00; optionally, 0<b≤0.6.

[0059] In some embodiments, in the general formula of the positive electrode material, a is, for example, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, 1.11, 1.12, b is, for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and b+c is, for example, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00.

[0060] In the present invention, it is preferred that the Li element is excessive, which is conducive to opening up the Li ion diffusion channel during the material synthesis process and improving the rate performance and first-cycle coulomb efficiency of the material. Insufficient amounts of other metal elements will cause the material to have a certain amount of MO6 (M mainly refers to Mn and Fe elements) octahedral vacancies, which can effectively reduce Fe-Li anti-site defects and provide storage space for excess Li, effectively accommodating excess Li atoms, so that the material is a pure LMFP olivine crystal phase without impurities.

[0061] In the present invention, the manganese iron content of the lithium manganese iron phosphate affects the slurry viscosity of the positive electrode material, and the positive electrode material with a low manganese content has a lower slurry viscosity.

[0062] In some embodiments, the average pore size of the positive electrode material is 40 nm ≤ d 平均 ≤55nm, optionally, 45nm≤d 平均 ≤55nm; for example, the average pore diameter is 40nm, 41nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm, 50nm, 51nm, 52nm, 53nm, 54nm, and 55nm.

[0063] In the present invention, the average pore size within this range indicates that the pore size of the positive electrode material is small, which is beneficial to reducing the slurry viscosity.

[0064] In some embodiments, the median pore size of the positive electrode material is 40 nm ≤ d 中位≤60nm; for example, the median pore diameter is 40nm, 41nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm, 50nm, 51nm, 52nm, 53nm, 54nm, 55nm, 56nm, 57nm, 58nm, 59nm, and 60nm.

[0065] In the present invention, the median of the aperture is the aperture in the middle after the apertures are arranged according to size, that is, the number of apertures smaller than the median of the aperture is equal to the number of apertures larger than the median of the aperture.

[0066] In the present invention, the median of the pore size is within this range, indicating that the pore size of the positive electrode material is small, which is beneficial to reducing the slurry viscosity.

[0067] In some embodiments, the compaction density of the positive electrode material is ≥2.0 g / cm 3 ; For example, the compaction density of the positive electrode material is 2.00g / cm 3 , 2.01g / cm 3 , 2.02g / cm 3 , 2.03g / cm 3 , 2.04g / cm 3 , 2.05g / cm 3 , 2.06g / cm 3 , 2.07g / cm 3 , 2.08g / cm 3 , 2.09g / cm 3 , 2.10g / cm 3 , 2.11g / cm 3 , 2.12g / cm 3 , 2.13g / cm 3 , 2.14g / cm 3 , 2.15g / cm 3 , 2.16g / cm 3 , 2.17g / cm 3 , 2.18g / cm 3 , 2.19g / cm 3 , 2.20g / cm 3 .

[0068] In the present invention, the compaction density of the positive electrode material is ≥2.0g / cm 3 After it is prepared into a battery, it is beneficial to improve the energy density of the battery.

[0069] In some embodiments, the specific surface area of ​​the positive electrode material is 10-27m 2 / g, optionally, 20-25m 2 / g. For example, the specific surface area is 10m2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, 24m 2 / g, 25m 2 / g, 26m 2 / g, 27m 2 / g.

[0070] In the present invention, if the specific surface area is too small, it is not conducive to the electrolyte wettability of the positive electrode material, and if the specific surface area is too large, the side reaction with the electrolyte is serious, which is not conducive to the battery life.

[0071] In some embodiments, the microscopic morphology of the positive electrode material is spherical secondary particles formed by stacking and combining primary particles. The interaction force between the spherical secondary particles is smaller than the interaction force between the crushed primary particles, so the spherical particles have better fluidity and can effectively reduce the slurry viscosity of the material.

[0072] In some embodiments, the positive electrode material is a pure phase LMFP olivine crystal phase. From the XRD diagram, it can be seen that there are no impurity peaks in the XRD curve, and the position and intensity of each diffraction peak are consistent with those on the lithium manganese iron phosphate standard card, indicating that the generated lithium manganese iron phosphate material is an olivine crystal form and has a very high phase purity.

[0073] The positive electrode material has a non-stoichiometric element ratio. Generally speaking, the non-stoichiometric element ratio is relatively easy to achieve. It only needs to adjust the relevant element ratio in the formula accordingly based on the loss and residual amount of the relevant elements in the process to obtain a non-stoichiometric lithium manganese iron phosphate positive electrode material. If you want the finished material to have the three-dimensional porous morphology and special pore structure of the present invention, you need to take corresponding process methods in a targeted manner.

[0074] As mentioned above, the second aspect of the present invention provides a method for preparing a positive electrode material, the method comprising: sequentially subjecting a slurry 1 containing a lithium source, a manganese source, an iron source, a phosphorus source and a first portion of a carbon source to a sand milling treatment I, a drying treatment I and a calcination treatment I to obtain a precursor;

[0075] The slurry 2 containing the precursor and the remaining carbon source is subjected to sand milling treatment II, drying treatment II and calcination treatment II in sequence to obtain the positive electrode material;

[0076] The first part of carbon source accounts for 40wt%-80wt% of the total carbon source.

[0077] In the present invention, the carbon source added in the first batching can generate amorphous carbon after the first sintering, and the amorphous carbon will be peeled off from the material surface during the second sanding process, and will be mixed with the primary particles of the positive electrode material during the second spraying process to form a compact primary particle accumulation, making the surface of the spherical particles more compact. The carbon source added in the second batching can effectively coat the surface of the positive electrode material that has been generated, thereby improving the conductivity of the material.

[0078] In some embodiments, the drying treatment I and the drying treatment II are spray drying treatments. The present invention has no special requirements for the specific operating steps of the spray drying treatment. For example, the material to be dried can be slowly transported to the feed inlet of the atomizer through a peristaltic pump, and the material to be dried can be atomized into droplets of qualified particle size, and then enter the drying tower to fully evaporate the water therein to obtain the spray-dried material.

[0079] Exemplarily, the first portion of carbon source accounts for 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, or 80wt% of the total carbon source; it can also be any value between 40wt% and 80wt%.

[0080] The present invention has no special requirements on the specific operations of the sand grinding treatment I and the sand grinding treatment II. For example, the slurry 1 or the slurry 2 can be introduced into a sand mill for sand grinding.

[0081] In some embodiments, the sanding treatment I is performed for 8 h to 12 h.

[0082] In some embodiments, the sanding treatment II is performed for 6 h to 10 h.

[0083] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide and lithium dihydrogen phosphate, the iron source includes at least one of ferric phosphate, ferrous oxalate, ferrous phosphate, and ferromanganese phosphate, the manganese source includes at least one of manganese tetraoxide, manganese phosphate, manganous oxalate, and ferromanganese phosphate, and the phosphorus source is at least one of ferric phosphate, lithium dihydrogen phosphate, phosphoric acid, and ferromanganese phosphate.

[0084] It is worth noting that when the iron source is iron phosphate, the phosphorus source such as lithium dihydrogen phosphate serves as a supplementary phosphorus source and a supplementary lithium source.

[0085] In some embodiments, the lithium source is lithium carbonate and lithium dihydrogen phosphate, the iron source is iron phosphate, the manganese source is manganese tetraoxide, and the phosphorus source is iron phosphate and lithium dihydrogen phosphate. The amount of lithium carbonate is 5wt%-20wt%, the amount of lithium dihydrogen phosphate is 15wt%-40wt%, the amount of iron phosphate is 35wt%-55wt%, and the amount of manganese tetraoxide is 5wt%-25wt%.

[0086] In some embodiments, the carbon source in slurry 1 and slurry 2 includes glucose and PEG; based on the total weight K of the lithium source, manganese source, iron source and phosphorus source in the slurry 1, the mass of glucose is 5%K-12%K, and the mass of PEG is 1%K-5%K; in some embodiments, the PEG is PEG6000. For example, based on the total weight K of the lithium source, manganese source, iron source and phosphorus source in the slurry 1, the mass of glucose is 5%K, 6%K, 7%K, 8%K, 9%K, 10%K, 11%K, 12%K. For example, based on the total weight K of the lithium source, manganese source, iron source and phosphorus source in the slurry 1, the mass of PEG is 1%K, 2%K, 3%K, 4%K, 5%K.

[0087] In some embodiments, the dispersant and / or solvent in slurry 1 includes water.

[0088] In some embodiments, the solid content of slurry 1 is 18wt%-48wt%. For example, the solid content of slurry 1 is 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%.

[0089] In some embodiments, the solid content of slurry 2 is 18wt%-48wt%. For example, the solid content of slurry 2 is 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%.

[0090] In some embodiments, the conditions of spray drying treatment I and spray drying treatment II are selected from: the inlet air temperature is 180-280°C, and the outlet air temperature is 60-160°C. For example, the inlet air temperature is 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C. For example, the outlet air temperature is 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C.

[0091] In some embodiments, the conditions of calcination treatment I and calcination treatment II are selected from: temperature of 300-800°C, time of 5-12h. For example, the calcination temperature is 300°C, 400°C, 500°C, 600°C, 700°C, 800°C. For example, the calcination time is 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h.

[0092] The present invention also provides a positive electrode material prepared by the above method.

[0093] As mentioned above, the third aspect of the present invention provides a lithium-ion battery, comprising the positive electrode material described in the first aspect and / or the positive electrode material prepared by the method described in the second aspect.

[0094] As mentioned above, the fourth aspect of the present invention provides an electrical device, comprising the lithium-ion battery as described in the third aspect.

[0095] In order to provide researchers in related fields with a deeper understanding of the present invention for obtaining a non-stoichiometric three-dimensional porous spherical manganese iron phosphate lithium positive electrode material with special pores, the following content will further illustrate the realization process of the relevant purpose of the present invention in combination with examples and comparative examples. Unless otherwise specified, the raw materials used are all common commercial products.

[0096] In the following examples and comparative examples, the total mass of lithium carbonate, lithium dihydrogen phosphate, iron phosphate and manganese tetraoxide is 100 parts by weight; in the following examples and comparative examples, each part by weight represents 10 g.

[0097] Embodiment 1:

[0098] Step 1: First batching: Use water as a dispersant, add 10.6 parts by weight of lithium carbonate, 27.6 parts by weight of lithium dihydrogen phosphate, 2.0 parts by weight of glucose and 3.0 parts by weight of PEG6000, and stir well at room temperature (25°C, the same below) to obtain a uniformly dispersed mixed slurry A.

[0099] 41.4 parts by weight of iron phosphate and 20.4 parts by weight of manganese tetraoxide were added to the mixed slurry A to obtain slurry 1 with a solid content of 30 wt%.

[0100] Step 2: First sand grinding: put the slurry 1 into a sand grinder and sand grind it for 10 hours to obtain the slurry after the first sand grinding.

[0101] Step 3: First spray drying: Place the slurry after the first sand grinding in a two-fluid spray drying equipment for the first spray drying, set the inlet air temperature to 260°C, and the outlet air temperature to 120°C to obtain the first spray dried material.

[0102] Step 4: First sintering: Place the first spray-dried particles in a box kiln and sinter them at 500°C for 6 hours to obtain a first-fired material, i.e., a precursor.

[0103] Step 5: Second batching: Using water as solvent, fully dissolve 5.0 parts by weight of glucose and 2.0 parts by weight of PEG6000 to obtain a mixed slurry B.

[0104] The precursor was added into the mixed slurry B and stirred thoroughly at room temperature to obtain slurry 2 with a solid content of 35 wt%.

[0105] Step 6: Second sand grinding: put slurry 2 into a sand grinder for sand grinding for 8 hours to obtain the slurry after the second sand grinding.

[0106] Step 7: Second spray drying: Place the slurry after the second sand grinding in a two-fluid spray drying equipment for a second spray drying, set the inlet air temperature to 260°C and the outlet air temperature to 120°C to obtain the second spray dried material.

[0107] Step 8: Second sintering: Sinter the spray-dried material for the second time at a sintering temperature of 780° C. for 8 hours to obtain a finished lithium manganese iron phosphate product.

[0108] The morphology of the product in Example 1 is as follows Figure 3 The porosity results are shown in Table 1.

[0109] Embodiment 2:

[0110] The preparation method of the positive electrode material provided in Example 2 is substantially the same as the preparation method of the positive electrode material provided in Example 1, and the difference lies in the content of glucose and PEG6000 added in step 1 and step 5:

[0111] Step 1: First batching: Use water as a dispersant, add 10.6 parts by weight of lithium carbonate, 27.6 parts by weight of lithium dihydrogen phosphate, 6.0 parts by weight of glucose and 3.0 parts by weight of PEG6000, and stir thoroughly at room temperature to obtain a mixed slurry A.

[0112] 41.4 parts by weight of iron phosphate and 20.4 parts by weight of manganese tetraoxide were added to the mixed slurry A to obtain slurry 1 with a solid content of 30 wt%.

[0113] Step 5: Second batching: Use water as solvent to fully dissolve 2.0 parts by weight of glucose and 1.0 parts by weight of PEG6000 to obtain a mixed slurry B.

[0114] The precursor was added into the mixed slurry B and stirred thoroughly at room temperature to obtain slurry 2 with a solid content of 35 wt%.

[0115] Embodiment 3:

[0116] The preparation method of the positive electrode material provided in Example 3 is substantially the same as the preparation method of the positive electrode material provided in Example 1, and the difference lies in the content of glucose and PEG6000 added in step 1 and step 5:

[0117] Step 1: First batching: Use water as a dispersant, add 10.6 parts by weight of lithium carbonate, 27.6 parts by weight of lithium dihydrogen phosphate, 6.0 parts by weight of glucose and 1.0 parts by weight of PEG6000, and stir thoroughly at room temperature to obtain a mixed slurry A.

[0118] 41.4 parts by weight of iron phosphate and 20.4 parts by weight of manganese tetraoxide were added to the mixed slurry A to obtain slurry 1 with a solid content of 30 wt%.

[0119] Step 5: Second batching: Using water as solvent, fully dissolve 3.0 parts by weight of glucose and 2.0 parts by weight of PEG6000 to obtain mixed slurry B.

[0120] The precursor was added into the mixed slurry B and stirred thoroughly at room temperature to obtain slurry 2 with a solid content of 35 wt%.

[0121] Embodiment 4:

[0122] The preparation method of the positive electrode material provided in Example 4 is basically the same as the preparation method of the positive electrode material provided in Example 1, except that the contents of the main ingredients (lithium carbonate, lithium dihydrogen phosphate, iron phosphate and manganese tetraoxide) in step 1 are different:

[0123] Step 1: First batching: Take water as a dispersant, add 8.7 parts by weight of lithium carbonate, 33.8 parts by weight of lithium dihydrogen phosphate, 2.0 parts by weight of glucose and 3.0 parts by weight of PEG6000, stir well at room temperature to obtain a uniformly dispersed mixed slurry A.

[0124] 51.2 parts by weight of iron phosphate and 6.3 parts by weight of manganese tetraoxide were added to the mixed slurry A to obtain slurry 1 with a solid content of 30 wt%.

[0125] Comparative Example 1:

[0126] The preparation method of the positive electrode material provided in Comparative Example 1 is substantially the same as the preparation method of the positive electrode material provided in Example 1, except that the content of glucose and PEG6000 added in step 1 and step 5 is:

[0127] Step 1: First batching: Using water as a dispersant, 10.6 parts by weight of lithium carbonate, 27.6 parts by weight of lithium dihydrogen phosphate, 10.0 parts by weight of glucose and 1.0 parts by weight of PEG6000 are added thereto, and mixed slurry A is obtained after sufficient stirring at room temperature.

[0128] 41.4 parts by weight of iron phosphate and 20.4 parts by weight of manganese tetraoxide were added to the mixed slurry A to obtain slurry 1 with a solid content of 30 wt%.

[0129] Step 5: Second batching: Use water as solvent to fully dissolve 0.5 parts by weight of glucose and 0.5 parts by weight of PEG6000 to obtain a mixed slurry B.

[0130] The precursor was added into the mixed slurry B and stirred thoroughly at room temperature to obtain slurry 2 with a solid content of 35 wt%.

[0131] Comparative Example 2:

[0132] The preparation method of the positive electrode material provided in Comparative Example 2 is substantially the same as that of the positive electrode material provided in Example 1, except that the content of glucose and PEG6000 added in Step 1 and Step 5 is:

[0133] Step 1: First batching: Using water as a dispersant, 10.6 parts by weight of lithium carbonate, 27.6 parts by weight of lithium dihydrogen phosphate, 2.0 parts by weight of glucose and 2.0 parts by weight of PEG6000 are added thereto, and mixed slurry A is obtained after sufficient stirring at room temperature.

[0134] 41.4 parts by weight of iron phosphate and 20.4 parts by weight of manganese tetraoxide were added to the mixed slurry A to obtain slurry 1 with a solid content of 30 wt%.

[0135] Step 5: Second batching: Using water as solvent, fully dissolve 6.0 parts by weight of glucose and 2.0 parts by weight of PEG6000 to obtain a mixed slurry B.

[0136] The precursor was added into the mixed slurry B and stirred thoroughly at room temperature to obtain slurry 2 with a solid content of 35 wt%.

[0137] Comparative Example 3:

[0138] The preparation method of the positive electrode material provided in Comparative Example 3 is substantially the same as the preparation method of the positive electrode material provided in Example 1, except that the content of glucose and PEG6000 added in step 1 and step 5 is:

[0139] Step 1: First batching: Using water as a dispersant, 10.6 parts by weight of lithium carbonate, 27.6 parts by weight of lithium dihydrogen phosphate, 1.0 parts by weight of glucose and 1.0 parts by weight of PEG6000 are added thereto, and mixed slurry A is obtained after sufficient stirring at room temperature.

[0140] 41.4 parts by weight of iron phosphate and 20.4 parts by weight of manganese tetraoxide were added to the mixed slurry A to obtain slurry 1 with a solid content of 30 wt%.

[0141] Step 5: Second batching: Using water as solvent, fully dissolve 7.0 parts by weight of glucose and 3.0 parts by weight of PEG6000 to obtain mixed slurry B.

[0142] The precursor was added into the mixed slurry B and stirred thoroughly at room temperature to obtain slurry 2 with a solid content of 35 wt%.

[0143] Comparative Example 4:

[0144] The preparation method of the positive electrode material provided in Comparative Example 4 is basically the same as the preparation method of the positive electrode material provided in Example 4, except that the contents of the main materials (lithium carbonate, lithium dihydrogen phosphate, iron phosphate and manganese tetraoxide) in step 1 are different:

[0145] Step 1: First batching: Using water as a dispersant, 8.7 parts by weight of lithium carbonate, 33.8 parts by weight of lithium dihydrogen phosphate, 1.0 parts by weight of glucose and 0 parts by weight of PEG6000 (i.e., without adding PEG6000) are added thereto, and mixed slurry A is obtained after sufficient stirring at room temperature.

[0146] 51.2 parts by weight of iron phosphate and 6.3 parts by weight of manganese tetraoxide were added to the mixed slurry A to obtain slurry 1 with a solid content of 30 wt%.

[0147] Step 5: Second batching: Using water as solvent, fully dissolve 7.0 parts by weight of glucose and 4.0 parts by weight of PEG6000 to obtain mixed slurry B.

[0148] The precursor was added into the mixed slurry B and stirred thoroughly at room temperature to obtain slurry 2 with a solid content of 35 wt%.

[0149] Comparative Example 5:

[0150] The preparation method of the positive electrode material provided in Comparative Example 5 is substantially the same as the preparation method of the positive electrode material provided in Example 1, except that the second sand grinding and the second spray drying are not performed, and the second sintering is performed directly:

[0151] The slurry 2 in step 5 is dried at a temperature of 200° C. and then directly sintered for the second time. The sintering temperature used is 780° C. and the holding time is 8 hours to obtain a finished lithium manganese iron phosphate product.

[0152] Comparative Example 6:

[0153] The difference between the preparation method of the positive electrode material provided in Comparative Example 6 and the preparation method in Example 1 is that only one sintering is performed:

[0154] Step 1: First, prepare the ingredients, that is, use water as a dispersant, add 10.6 parts by weight of lithium carbonate, 27.6 parts by weight of lithium dihydrogen phosphate, 6.0 parts by weight of glucose and 6.0 parts by weight of PEG6000, and stir well at room temperature to obtain a uniformly dispersed mixed slurry A.

[0155] 41.4 parts by weight of iron phosphate and 20.4 parts by weight of manganese tetraoxide were added to the mixed slurry A to obtain slurry 1 with a solid content of 30 wt%.

[0156] Step 2: Then, sand milling is performed. The slurry 1 is put into a sand mill and sand milled for 10 hours to obtain the sand milled slurry.

[0157] Step 3: spray drying is performed again. The sand-milled slurry is placed in a two-fluid spray drying device for spray drying. The inlet air temperature is set to 260° C. and the outlet air temperature is set to 120° C. to obtain a spray-dried material.

[0158] Step 4: Finally, sintering is performed. The spray-dried material is placed in a box kiln and sintered at 780°C for 8 hours to obtain a finished lithium manganese iron phosphate product.

[0159] In the present invention, the pore size, pore volume and specific surface area of ​​the positive electrode materials prepared in the above embodiments and comparative examples are measured by nitrogen adsorption-desorption method. The specific test method refers to the national standard (GB / T7702.20-2008). The test results are shown in Table 1.

[0160] In the pore size test of the present invention, since the test method cannot accurately test pore sizes below 2 nm, the pore size distribution in the following embodiments and comparative examples is 2-200 nm.

[0161] Table 1: Physical and chemical indicators of positive electrode materials in examples and comparative examples

[0162]

[0163] Table 1 (Continued)

[0164]

[0165]

[0166] Figure 4 The XRD patterns of the lithium manganese iron phosphate cathode materials prepared in Example 1 and Comparative Example 1 are shown. Figure 4 It can be seen that the materials prepared in Example 1 and Comparative Example 1 are both pure-phase lithium manganese iron phosphate.

[0167] The positive electrode materials, binder (PVDF) and conductive agent (SP) in the above-mentioned embodiments and comparative examples were placed in a slurry kettle at a mass ratio of 8:1:1, and NMP was added and stirred for 8 hours. The viscosity of the stirred slurry was tested as shown in Table 2.

[0168] The stirred slurry was coated on aluminum foil to make a positive electrode sheet, a metal lithium sheet was used as a negative electrode sheet, and the electrolyte was 1 mol / L LiPF6 / EC:DMC:EMC (volume ratio of 1:1:1). The battery shell, positive and negative electrode sheets, diaphragms, springs, and gaskets were assembled into button batteries in a vacuum glove box. The Blue Electric test system was used to test 0.1C and 1C (the specific capacity used for calculating the current was 170 mAh g) at a voltage of 2.0-3.75 V. -1 ) was tested for charge and discharge, and the results are shown in Table 2.

[0169] in addition, Figure 5 The rate performance curve of the lithium manganese iron phosphate positive electrode material prepared in Example 1 is shown. Figure 5 It can be seen that the lithium manganese iron phosphate prepared in Example 1 has a higher rate performance, and the 1C discharge specific capacity is 146 mAh / g.

[0170] Figure 6 The rate performance curve of the lithium iron manganese phosphate positive electrode material prepared in Comparative Example 1 is shown. Figure 6 It can be seen that the rate performance of the lithium manganese iron phosphate prepared in Comparative Example 1 is lower than that in Example 1, and the 1C discharge specific capacity is 141 mAh / g.

[0171] Table 2: Slurry viscosity and electrochemical performance data of positive electrode materials in Examples and Comparative Examples

[0172]

[0173]

[0174] For different embodiments and comparative examples, the corresponding change rules of pore structure and processing performance are the same, so Example 1, Example 2 and Comparative Example 1, Comparative Example 2 are used as demonstrations here to analyze the corresponding rules of pore structure and slurry effect.

[0175] As can be seen from Table 1, the pore size distribution range of the positive electrode materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 is the same, but the pore volume proportion of different pore sizes is significantly different. The pore size d of the positive electrode materials prepared in Example 1 and Example 2 in the range of 2-100nm and 100-200nm accounts for 78.4%, 21.6% and 87.0%, 13.0% respectively. The pore size distribution d of Comparative Example 1 and Comparative Example 2 in the range of 2-100nm and 100-200nm accounts for 58.1%, 41.9% and 65.6%, 34.4% respectively. This shows that although the pore size distribution range of the spherical positive electrode materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 is the same, all 2-200nm, the pore size distribution range of Example 1 and Example 2 is more concentrated in the range of 2-100nm, while the distribution of Comparative Example 1 and Comparative Example 2 in the range of 2-100nm is less, and the proportion of macropores in the range of 100-200nm is significantly higher.

[0176] From the slurry viscosity results of different positive electrode materials, it can be seen that the slurry viscosities of Example 1 and Example 2 are 2777.0 mPa·s and 2573.0 mPa·s, respectively, and have excellent processing performance. However, the slurry viscosities of Comparative Example 1 and Comparative Example 2 are 7487.0 mPa·s and 7510.0 mPa·s, respectively, which are very high in viscosity and have poor processing performance.

[0177] Since more pores can improve the contact between the electrolyte and the positive electrode material, and can improve the electrochemical performance of the material, the field requires that the positive electrode material has more pores. However, in the slurrying process of the pole piece, the larger pore size will excessively adsorb the binder, making the slurry viscosity of the material too high and the processing performance very poor. Taking all factors into consideration, on the one hand, in order to improve the electrochemical performance of the material, it is necessary to prepare the material into a porous structure; on the other hand, in order to ensure the processing performance of the material, by adopting the above-mentioned process, the positive electrode material is prepared into a three-dimensional porous structure with a smaller proportion of 100-200nm macropores as described in the present invention, so that the material has excellent electrochemical properties while showing good processing performance. It can be seen that the process method described in the present invention can effectively reduce the slurry viscosity of the positive electrode material and significantly improve the processing performance of the material.

[0178] In addition, the microstructure of the positive electrode material will also affect the slurry viscosity of the positive electrode material.

[0179] like Figure 1As shown in a in the figure, the sphericity of the positive electrode material prepared in Example 1 is low, but the primary particles are densely packed and there are no obvious macropores between the particles. Figure 1 As shown in c, the sphericity of the positive electrode material prepared in Comparative Example 1 is better than that of the positive electrode material prepared in Example 1, but the stacking between the primary particles is looser and there are more macropores. Example 2 has the same morphology change trend as Comparative Example 2.

[0180] like Figure 2 As shown in a in the figure, the positive electrode material prepared in Example 1 has a relatively smooth profile due to the dense accumulation of primary particles. Figure 2 As shown in c, due to the loose primary particle accumulation of the positive electrode material prepared in Comparative Example 1, its profile is rougher than that of the positive electrode material prepared in Example 1, which will greatly increase the slurry viscosity of the material. The positive electrode materials prepared in Example 2 and Comparative Example 2 also have the same trend in spherical profile.

[0181] The lithium manganese iron phosphate positive electrode materials prepared in the present invention all show high capacity, initial charge and discharge efficiency and rate performance, which is mainly attributed to their special spherical shape and pore structure morphology.

[0182] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material includes lithium manganese iron phosphate; the total pore volume of the positive electrode material is V 总 ≥0.25cm 3 / g; the proportion of the pore volume of the positive electrode material with a pore size between 0-100nm to the total pore volume is W d(0-100) , W of the positive electrode material d(0-100) ≥70%.

2. The positive electrode material according to claim 1, characterized in that The pore size distribution of the positive electrode material is 0nm≤d≤200nm; And / or, the total pore volume of the positive electrode material is 0.25≤V 总 ≤0.5cm 3 / g; and / or, W of the positive electrode material d(0-100) ≥80%.

3. The positive electrode material according to claim 1, characterized in that The positive electrode material also includes a carbon material; Preferably, based on the total weight of the positive electrode material, the content of the carbon material is 1.7 wt% to 2.5 wt%.

4. The positive electrode material according to claim 1, characterized in that The lithium manganese iron phosphate has the general formula Li a Mn b Fe c PO4 represents, wherein, 1.00≤a≤1.12, b>0, 0.94≤b+c≤1.00; preferably, 0<b≤0.

6.

5. The positive electrode material according to any one of claims 2 to 4, characterized in that: The positive electrode material satisfies at least one of the following conditions: Condition a: The average pore size of the positive electrode material is 40nm≤d 平均 ≤55nm, preferably 45nm≤d 平均 ≤55nm; Condition b: The median pore size of the positive electrode material is 40nm≤d 中位 ≤60nm; Condition c: The compaction density of the positive electrode material is ≥ 2.0 g / cm 3 ; Condition d: The specific surface area of ​​the positive electrode material is 10-27m 2 / g, preferably 20-25m 2 / g.

6. A method for preparing a positive electrode material, characterized in that: The method comprises: The slurry 1 containing the lithium source, the manganese source, the iron source, the phosphorus source and the first part of the carbon source is subjected to sand milling treatment I, drying treatment I and sintering treatment I to obtain a precursor; The slurry 2 containing the precursor and the remaining carbon source is subjected to sand milling treatment II, drying treatment II and sintering treatment II to obtain the positive electrode material; The first part of carbon source accounts for 40wt%-80wt% of the total carbon source.

7. The method according to claim 6, characterized in that The total carbon sources include glucose and PEG; Preferably, based on the total weight K of the lithium source, manganese source, iron source, and phosphorus source in the slurry 1, the mass of the glucose is 5%K-12%K, and the mass of the PEG is 1%K-5%K.

8. The method according to claim 6 or 7, characterized in that: The method satisfies at least one of the following conditions: Condition A: The solid content of the slurry 1 is 18wt%-48wt%; Condition B: The sanding treatment I is performed for 8-12 hours; Condition C: the solid content of the slurry 2 is 18wt%-48wt%; Condition D: The sanding treatment II is performed for 6 h to 10 h; Condition E: the drying treatment I and the drying treatment II are spray drying treatments; preferably, the conditions of the spray drying treatment are selected from: an inlet air temperature of 180-280°C and an outlet air temperature of 60-160°C; Condition F: The conditions of the sintering treatment I and the sintering treatment II are selected from: temperature of 300-800° C. and time of 5-12 h.

9. A lithium ion battery, characterized in that: The invention comprises the positive electrode material as claimed in any one of claims 1 to 5 and / or the positive electrode material prepared by the method as claimed in any one of claims 6 to 8.

10. An electrical equipment, characterized in that: Comprising the lithium ion battery as claimed in claim 9.